12.7-3t=13.39

Simple and best practice solution for 12.7-3t=13.39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12.7-3t=13.39 equation:


Simplifying
12.7 + -3t = 13.39

Solving
12.7 + -3t = 13.39

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-12.7' to each side of the equation.
12.7 + -12.7 + -3t = 13.39 + -12.7

Combine like terms: 12.7 + -12.7 = 0.0
0.0 + -3t = 13.39 + -12.7
-3t = 13.39 + -12.7

Combine like terms: 13.39 + -12.7 = 0.69
-3t = 0.69

Divide each side by '-3'.
t = -0.23

Simplifying
t = -0.23

See similar equations:

| 11.5y+16.7=23.6 | | 4-2/3= | | 4-2/3=× | | 295065-(2.2*131700)= | | 7x+5=3x+40 | | 2.5n+7=9 | | 5x^2-18x-27=0 | | 4-(2/3)=× | | y=-7+-6x | | 25x+5(70+x)+10(x+70+20)=6850 | | 6x+5z=7+5y | | 10x+12=150 | | (h)t=20-16t^2+32t | | 25x+10x+5(20+x)=1300 | | -2+11x=81 | | (2y+7)(1-y)=0 | | 4(7y-9)-(5y+5)= | | (4x-5)/(3x-2) | | ((5x-10)/7)/((7x-14)/5)= | | 3x-(-x+5)=9 | | -2(4x-4)=2 | | 2x+5=50-x | | 5n^2+27n+10= | | (7s-1)(8s+3)= | | -4y+2=-2(3y+7) | | 25x+10(86-x)=1460 | | 16x^2-72x+1024=0 | | -16t^2-961=0 | | (13f^3-9f^2+7f-16)-(-8f^3+5f^2+9f-4)= | | p=300/.1*(120/12) | | 2ab+4ab-5c= | | 10x-8=9(x+3)-7 |

Equations solver categories